The Futile Creatine Cycle powers UCP1-independent thermogenesis in classical BAT - Jakub Bunk; Mohammed F. Hussain; Maria Delgado-Martin; Bozena Samborska; Mina Ersin; Abhirup Shaw; Janane F. Rahbani; Lawrence Kazak (Nature Communications)
Abstract Classical brown adipose tissue (BAT) is traditionally viewed as relying exclusively on uncoupling protein 1 (UCP1) for thermogenesis via inducible proton leak. However, the physiological significance of UCP1-independent mechanisms linking substrate oxidation to ATP turnover in classical BAT has remained unclear. Here, we identify the Futile Creatine Cycle (FCC), a mitochondrial-localized energy-wasting pathway involving creatine phosphorylation by creatine kinase b (CKB) and phosphocreatine hydrolysis by tissue-nonspecific alkaline phosphatase (TNAP), as a key UCP1-independent thermogenic mechanism in classical BAT. Reintroducing mitochondrial-targeted CKB exclusively into interscapular brown adipocytes in vivo restores thermogenesis and cold tolerance in mice lacking native UCP1 and CKB, in a TNAP-dependent manner. Furthermore, mice with inducible adipocyte-specific co-deletion of TNAP and UCP1 exhibit severe cold-intolerance. These findings challenge the view that BAT thermogenesis depends solely on UCP1 because of insufficient ATP synthase activity and establishes the FCC as a physiologically relevant thermogenic pathway in classical BAT.